External intervention and responsive adaptation by the community: Experiences of improving house quality in an urban slum - Imon Chowdhooree; Ishrat Islam (Journal of Flood Risk Management)
Abstract Non‐governmental organizations (NGOs), governmental organizations, or other entities may run their projects as external interventions within a community to reduce disaster risks and adapt to future climatic events. These external interventions may influence the community to take further adaptation measures for enhancing community resilience. The spontaneous adaptation process, referring as responsive adaptation, needs to be identified and acknowledged. This research aims to investigate the impacts of external interventions on the responsive adaptation process by studying a riverside flood‐prone urban slum in Bangladesh. This settlement experienced a site development project, primarily run by an NGO, that allowed several modifications to the built environment, mainly targeting flood risks. Selected tools of participatory rural appraisal (PRA) or participatory urban appraisal (PUA) methods were employed to obtain data about the community's initiatives for further development. The results show that the site development project, especially its impacts on reducing flood risks, has influenced community members to invest in improving the condition of their individual houses. As a means of responsive adaptation, the conscious developments of their houses contribute to enhancing the resilience level. Through exploring the community's initiatives, this research identifies that the engagement of communities with their knowledge and investments can extend the success of the external intervention.